Kinetic Studies on the Removal of Some Lanthanide Ions from Aqueous Solutions Using Amidoxime-Hydroxamic Acid Polymer - Fadi Alakhras (Journal of Analytical Methods in Chemistry)
Lanthanide metal ions make distinctive and essential contributions to recent global proficiency. Extraction and reuse of these ions is of immense significance especially when the supply is restricted. In light of sorption technology, poly(amidoxime-hydroxamic) acid sorbents are synthesized and utilized for the removal of various lanthanide ions (La3+, Nd3+, Sm3+, Gd3+, and Tb3+) from aqueous solutions. The sorption speed of trivalent lanthanides (Ln3+) depending on the contact period is studied by a batch equilibrium method. The results reveal fast rates of metal ion uptake with highest percentage being achieved after 15–30 min. The interaction of poly(amidoxime-hydroxamic) acid sorbent with Ln3+ ions follows the pseudo-second-order kinetic model with a correlation coefficient R2 extremely high and close to unity. Intraparticle diffusion data provide three linear plots indicating that the sorption process is affected by two or more steps, and the intraparticle diffusion rate constants are raised among reduction of ionic radius of the studied lanthanides.